Diagnostic Performance of Parasitological, Immunological, Molecular, and Ultrasonographic Tests in Diagnosing Intestinal Schistosomiasis in Fieldworkers From Endemic Municipalities in the Philippines - Tabios, Ian Kim B.; Sato, Marcello Otake; Tantengco, Ourlad Alzeus G.; Fornillos, Raffy Jay C.; Kirinoki, Masashi; Sato, Megumi; Rojo, Raniv D.; Fontanilla, Ian Kendrich C.; Chigusa, Yuichi; Medina, Paul Mark B.; Kikuchi, Mihoko; Leonardo, Lydia R. (Frontiers in Immunology, 2022)
Schistosomiasis remains to have a significant public health impact in the Philippines. The Kato-Katz (K-K) technique is the reference standard and most used technique for definitive diagnosis of intestinal schistosomiasis for control programs in endemic regions. However, this has a very low sensitivity when applied in areas of low endemicity and patients with light infection. Hence, this study determined the diagnostic performance of immunological, molecular, parasitological, and ultrasonographic tests in diagnosing intestinal schistosomiasis in endemic municipalities in the Philippines. We performed a community-based cross-sectional study to determine the positivity of schistosomiasis in Leyte, Philippines. The diagnostic performance of five different detection techniques: (1) three stool K-K with duplicate smears; (2) soluble egg antigen IgG ELISA; (3) urine point-of-care circulating cathodic antigen (POC-CCA) test; (4) detection of Schistosoma japonicum circulating DNA (SjcDNA) in serum and urine samples; (5) focused abdominal ultrasound (US), were also obtained in this study. Multiple stool examinations enhanced the sensitivity of K-K from 26.2 % (95% CI [16.4, 38.8]) with single stool to 53.8 % (95% CI [41.1, 66.1]) and 69.2 % (95% CI [56.4, 80.0]) with two and three stools from consecutive days, respectively. Among the SjcDNA nucleic acid amplification test (NAAT)-based detection assays, loop-mediated isothermal amplification (LAMP) PCR using sera had the highest sensitivity at 92.3 % (95% CI [82.2, 97.1]) with LAMP consistently identifying more positive cases in both serum and urine samples. This study showed that single stool K-K, which remains the only diagnostic test available in most endemic areas in the Philippines, had low sensitivity and failed to identify most patients with light infection. SjcDNA detection assay and POC-CCA urine test were more sensitive than stool microscopy in detecting schistosomiasis. On the other hand, US was less sensitive than the widely utilized K-K technique in diagnosing schistosomiasis. This study emphasizes the need to revisit the use of single stool K-K in the surveillance and case detection of schistosomiasis in endemic areas of the Philippines. The availability of advanced and more sensitive diagnostic tests will help better control, prevent, and eliminate schistosomiasis in the country.